The Perceptions of Residents and Businesses towards the Sustainable Development of Tourism - DAUTI, Merita Begolli; DAUTI, Rron; KRASNIQI, Musa; NISHIQI, Dukagjin (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
Among the economic benefits of tourism development, the negative environmental and socio-cultural impacts caused during tourism activities should be taken into account and carefully managed. In achieving sustainability in the development of tourism, residents, and businesses - tourism service providers should have the right to identify and express concerns and determine the pace and degree of development. The purpose of this study was to identify and analyze the importance of negative and positive economic, socio-cultural and environmental impacts of tourism, based on the perceptions of residents and businesses on the scale of importance, which is a possible action to boost tourism development sustainably. This quantitative study, based on a random sample, was conducted in Kosovo’s territory, using a questionnaire addressed to 338 residents and 221 businesses. The questionnaire results were analysed using the RII test - Relative importance index and the Mann-Whitney test. This study intended to bridge the gap by measuring residents and businesses’ perceptions on sustainable tourism development and their suggestions to promote it.